تحليل الأخطاء الكتابية الإملائية في تعليمات المنتجات الإندونيسية - Achmad Muhlis; Umi Alifatil Azizah (IAIN MADURA, 2017)
This article describes errors of writing found in ingredients of Indonesian products which are written in Arabic, for example ingredients of foods or snacks based on imla’ and non-imla’ perspective. After doing depth analysis of errors in ingredients writing, it is found that there are some errors. From Imla’ perspective, the errors are: (1) the placement of hamzah in the beginning, in the middle, and in the end of words. (2) hamzah qatha’ and hamzah washal (3) punctuations such as comma [,] full stop [.], and etc. Furthermore, based on non-imla’ perspective, the errors are: (1) the change of letter is caused by equality of sound so that it is heared the same writing, (2) another errors happen because of addition of letter in certain words which result other words that are different from Arabic dictionary, (3) The last, the errors resulted from reduction of some letter(s) in certain words in which it is literally different from dictionary meaning and do not follow the correct rule of Arabic writing.